EFREMOVKA 101.1: A CAI WITH ULTRAREFRACTORY REE PATTERNS AND ENORMOUS ENRICHMENTS OF SC, ZR, AND Y IN FASSAITE AND PEROVSKITE - El Goresy A.; Spettel B.; Zinner E.; Matsunami S.; Palme H.; Lin Y.; Nazarov M. (My University, 2002)
Inclusion 101.1 from the CV3 carbonaceous chondrite Efremovka is a compact Type A Ca-Al-rich inclusion (CAI) highly enriched in ultrarefractory (UR) oxides. It is the first complete CAI with a UR rare earth element (REE) pattern found in a CV3 chondrite. The inclusion is petrographically complex and was formed in a multistage process. It consists of several lithologically unrelated units.The core contains abundant Y- and Zr-perovskite, Sc- and Zr-rich fassaite, and metallic FeNi enclosed in melilite. All mineral species (except spinel) in all lithological units exhibit the same basic UR REE pattern. Four different populations of perovskites are distinguished by different Y/Zr ratios. A few of the perovskites have Y/Zr ratios similar to those obtained from crystal/liquid fractionation experiments. Perovskites from the other three populations have either chondritic, lower than chondritic Y/Zr ratios or extremely low Zr contents. Ca isotopic ratios differ among three perovskites from different populations, demonstrating a variety of sources and formational processes. Most fassaites crystallized in situ through reaction between the CAI liquid and preexisting perovskites. This process induced redistribution of Zr, Y, Sc, and V between perovskite and fassaite, thus overprinting the original abundances in perovskite. Fassaite reaction rims around FeNi metals are also encountered. They are enriched in V, which was gained from the metal through oxidation of V in metal during fassaite crystallization. The relative abundances of Zr, Y, and Sc in perovskites are complementary to the abundances of these elements in Sc- and Zr-fassaite, indicating subsolidus partitioning of these elements between the two phases. Perovskites are enriched in Y and depleted in Sc and Zr in comparison to fassaites.The core contains two complete captured CAIs, several sinuous fragments, and fine-grained polygonal refractory fragments. An assemblage of andradite-wollastonite-hedenbergite and pure metallic iron is encountered as enclaves in the interior of some sinuous fragments. Metallic Fe and wollastonite formed by reduction of preexisting andradite and hedenbergite nebular alteration products upon inclusion in the highly reduced CAI melt. Numerous spinel clusters and framboids with varying V2O3 and Cr2O3 concentrations are enclosed in individual melilite crystals in the host CAI and captured CAIs. The rim sequence of the host consists of six layers (from the inside outward): (a) FeO-poor spinel, (b) Sc-bearing fassaite, (c) Al-diopside, (d) Al- and Ca-bearing olivine, (e) pure diopside, and (f) Ca-poor olivine. Like the constituents of the CAI core, all mineral layers of the rim sequence, except spinel, have the same UR REE pattern. However, the total REE abundances decrease systematically by 1 order of magnitude from layer 2 to layer 6. This feature strongly suggests formation of the rim sequence by successive condensation from a unique reservoir enriched in UR elements and excludes formation by flash heating. Petrography, mineral chemistry, REE, refractory lithophile element abundances, and Ca isotopic compositions demonstrate the complex multistage formation history of a CAI that on the surface looks like a regular Type A inclusion.